FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN MAHASISWA DALAM MENYEWA TEMPAT TINGGAL DI KAMPUS INSTITUT PERTANIAN BOGOR DRAMAGA (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2021)
Bogor Agricultural University (IPB) Dramaga is one of the universities with the best agricultural background in Indonesia. Many people are willing to leave for education at IPB. However, many of the overseas students have problems regarding where to live. The purpose of this study (1) To identify the factors that influence the rental of temporary housing in the Bogor Agricultural University area. (2) Analyze the factors that influence the decision to lease a temporary residence while studying at the Dramaga Bogor Agricultural University. The type of data in this study is quantitative data, primary data is obtained through questionnaires and secondary data is obtained from the Bogor Agricultural University website, as well as various relevant literature and reports. The method used is descriptive analysis and factor analysis with the variables used in this study is the 7P Marketing Mix. Based on the results of the factor analysis, 20 new factors were formed that greatly influenced consumers in choosing a temporary residence. In addition, the alternative that can be given from this research is that the owner of the residence should be able to optimize the promotion in terms of advertising so that it is right on target.Keywords:IPB Students, Marketing Mix, Temporary Residence